Investigating Mechanical Properties of Hybrid Polymer Composite Reinforced with S-Glass and Luffa Fibres. Issue 1 (1st July 2022) - Vigneshkumar, N.; Harikannan, N.; Selvakumar, S; Manoj Kumar, P.; Subbiah, Ram; Saravanakumar, P.T.
Abstract: The mix of two different type of fibres, one is natural and another one is synthetic fibres were employed as reinforcing media in this study, and epoxy based polymer resin was employed as the matrix phase. S-glass and luffa fibres had been bonded with epoxy matrix to create a novel composite by compression moulding and to measure the effect of this hybridization in composite laminate utilising five different sequencing. To determine the mechanical characteristics of this composite material using tensile, flexural, and compression strength, a specimen named 'SL4' had shown the highest mechanical strength, resulting in a tensile properties of 253 MPa, compression strength of 234 MPa, and flexural characteristics of 237 MPa. The increment in mechanical characteristics is found to exhibiting around 20% increase comparing to the specimen having next higher value in all the properties. The results evidenced that the presence of luffa fibre layers at the interior most portion of the composite displayed the progressive values in all the investigated mechanical characteristics.